Effect of freeze-thaw cycles on bending properties and microstructure of slag-fly ash based geopolymer cemented iron tailings sand - Hongchun Xu; Hang Yin; Shasha Lu; Ge Pei (Case Studies in Construction Materials, 2025)
This study aims to reveal the damage characteristics of slag-fly ash cemented iron tailings sand controlled low-strength material (SFG-T-CLSM) under freeze-thaw cycles, as well as the mechanism of fibers enhancing the durability performance in SFG-T-CLSM. Through three-point bending tests, CT scanning tests, and scanning electron microscopy (SEM) tests, the microstructural changes and macro-mechanical property responses of fiber-reinforced SFG-T-CLSM in freeze-thaw environments were comprehensively analyzed. The research results show that: with the increase in the number of freeze-thaw cycles, the flexural strength of SFG-T-CLSM gradually decreases. After 15 freeze-thaw cycles, the flexural strength loss of the specimen without fiber addition is 43.84 %, while the strength loss decreases to 29.10 % after adding 5 ‰ fibers. Three-dimensional reconstructed CT slices reveal that the number of pores inside the matrix gradually increases. However, the presence of fibers during freeze-thaw cycles effectively alleviates pore development, plays a role in bridging cracks and dispersing stress, improves the pore distribution characteristics inside the CLSM matrix, significantly reduces the number and width of cracks, and remarkably enhances the crack resistance of SFG-T-CLSM. SEM results further confirm that fibers exhibit significant anti-damage effects in SFG-T-CLSM under harsh freeze-thaw cycle environments through their three-dimensional network structure. The debonding mode of fibers gradually evolves with the increase in the number of freeze-thaw cycles: from good bonding in the early stage, to interfacial damage in the middle stage, and then to significant debonding in the later stage. Consequently, the role of fibers in SFG-T-CLSM gradually weakens, and the crack resistance and structural integrity also decline accordingly. This study demonstrates that the introduction of fibers is an effective strategy to enhance the freeze-thaw durability of CLSM, providing a theoretical basis for improving the application of CLSM in extreme environments.